Batas Tumpang Tindih Epistemik: Konstruksi Historis-Diskursif Gaib dalam Hadis Sunni-Syi’ah - Muhammad Iqbal Rahman; Hubul Hoir; Sukma Sari Dewi Chan; Baharudin Baharudin; Rizkiyadi Rizkiyadi (ASILHA (Asosiasi Ilmu Hadis Indonesia), 2026)
This study examines how hadiths concerning God, angels, and divine decree construct epistemic authority within Sunni and Shi’a traditions and how their theological convergence remains constrained by different mechanisms of interpretation. The study employs a qualitative method using library research with a descriptive-analytical-comparative approach. Primary data were purposively selected from Ṣaḥīḥ al-Bukhārī, Ṣaḥīḥ Muslim, and al-Kāfī, focusing on representative reports within the three thematic clusters, while Mir’āt al-‘Uqūl and classical Qur’anic commentaries serve as interpretive sources. Data were analyzed through historical-critical contextualization, Reisigl and Wodak’s Discourse-Historical Approach (DHA), and Ricoeur’s hermeneutics, particularly the dialectic of distanciation and appropriation. The findings demonstrate that both traditions converge at the level of fundamental metaphysical principles, particularly divine transcendence, angelic existence, and divine determination, yet diverge in the mechanisms through which epistemic authority is established. Sunni discourse tends to articulate truth through relational praxis, ritual participation, and religious experience, whereas Shi’a discourse emphasizes ontological consistency and the epistemic authority of the Imam. The study argues that Sunni-Shi’a overlap is multilayered rather than identical. Consequently, critical theological dialogue requires recognition of shared principles without erasing the historical and discursive asymmetries through which each tradition authorizes knowledge of the unseen.